2017
DOI: 10.1017/s030500411700069x
|View full text |Cite
|
Sign up to set email alerts
|

Presentations for (singular) partition monoids: a new approach

Abstract: We give new, short proofs of the presentations for the partition monoid and its singular ideal originally given in the author's 2011 papers in J. Alg. and I.J.A.C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…It also follows from some of the above identities. We will also require the following result from [37]; see also [44,46]. For 1 ≤ i ≤ n, let π i ∈ P n be the projection with domain [n] \ {i} and kernel ∆.…”
Section: The Partition Monoidmentioning
confidence: 99%
See 1 more Smart Citation
“…It also follows from some of the above identities. We will also require the following result from [37]; see also [44,46]. For 1 ≤ i ≤ n, let π i ∈ P n be the projection with domain [n] \ {i} and kernel ∆.…”
Section: The Partition Monoidmentioning
confidence: 99%
“…The original study of cellular semigroup algebras may be found in [35]; see also [73,74,112,113] for some recent developments. Another example of how the study of these semigroups can give information about the associated algebras may be found in work of the first author [36], who gives presentations for the partition monoid and shows how these presentations give rise to presentations for the partition algebra; see also [37,43,44]. A further example is given in the paper [27] where idempotents in the partition, Brauer and partial Brauer monoids are described and enumerated, and then the results are applied to determine the number of idempotent basis elements in the finite dimensional partition, Brauer and partial Brauer algebras; see also [28].…”
Section: Introductionmentioning
confidence: 99%
“…For Assumption 2, we take the partitions λ n ∈ P n,n+1 and ρ n ∈ P n+1,n shown in Figure 3; clearly λ n ρ n = ι n for all n ∈ N. For Assumption 3, we require presentations for the partition monoids P n (n ∈ N). Such presentations are stated in [40]; proofs may be found in [29,30]. First, for n ∈ N define an alphabet…”
Section: The Partition Categorymentioning
confidence: 99%
“…Theorem 3.1 (cf. [29,30,40]). For any n ∈ N, the partition monoid P n has presentation X n : R n via φ n .…”
Section: The Partition Categorymentioning
confidence: 99%
See 1 more Smart Citation